Recovery strategy of distribution network based on dynamic island rescue under extreme weather - Xinrui Liu; Qingkun Meng; Rui Wang; Chaoyu Dong; Qiuye Sun (IET Energy Systems Integration)
Abstract The frequent occurrence of various extreme weather has a great influence on the normal and stable operation of the distribution network. In order to minimise the large‐scale power loss of the distribution network caused by extreme weather, considering that most of the practical disasters are concurrent with various weather types, and each disaster is independent of each other. A unified failure rate calculation model is proposed, which includes line break, short circuit, tower fall, insulator flashover etc., to realise disaster scenario prediction. Secondly, a resilience evaluation index of island rescue based on mobile energy storage system (IR‐MESS) is proposed. Thirdly, considering the flexibility of MESS, the pre‐disaster scheduling of MESS is carried out according to the predicted disaster scenario. After the disaster occurs, a spatio‐temporal optimisation scheduling model based on the rescue state and charge state of MESS is proposed, and a dynamic IR‐MESS is formed to provide power supply for important loads in out‐of‐load areas of the distribution network. Finally, taking the actual ice disaster in northeast China as an example, the results show that the rescue strategy based on IR‐MESS proposed in this paper can effectively elevate the resilience of the distribution network.